Retrofitting vectors for Escherichia coli-based artificial chromosomes (PACs and BACs) with markers for transfection studies. - Mejía, J E; Monaco, A P (Genome Research, 1997)
P1-based artificial chromosomes (PACs) and bacterial artificial chromosomes (BACs) have significantly expanded the size of fragments from eukaryotic genomes that can be stably cloned in Escherichia coli as plasmid molecules. Functional characterization of a gene within a given PAC or BAC clone often requires transferring the DNA into eukaryotic cells for transient or long-term expression. To facilitate transfection studies, we have developed protocols using the Notl restriction sites of any PAC or BAC clone to introduce a transfection reporter gene, lacZ, together with a selectable marker, neo. This enables transfected cells to be detected by X-Gal staining to verify DNA uptake, and clones of stably transformed cells may be selected for in the presence of the antibiotic G418. The same retrofitting protocols may be applied with other markers of interest to extend the functionality of PAC and BAC libraries, and specialized aspects of such manipulation of E. coli-based artificial chromosomes are outlined.